2009
DOI: 10.3892/or_00000252
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the histone deacetylase inhibitor valproic acid on the sensitivity of anaplastic thyroid cancer cell lines to imatinib

Abstract: Abstract. New therapeutic approaches are mandatory for anaplastic thyroid cancer. We investigated the ability of a new combined treatment using valproic acid (VPA), the only clinically available histone deacetylase inhibitor, and the tyrosine-kinase inhibitor imatinib mesylate to control the cell growth of anaplastic thyroid cancer cell lines. We showed that treatment with imatinib alone is unable to affect the cell growth of anaplastic thyroid cancer cells, whereas in ARO cells, the combined treatment resulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…One study found that treatment with imatinib alone was not able to grow anaplastic cells in thyroid cancer cells, but that combination therapy (imatinib and VPA) had a cytostatic effect. This effect is mediated by stunted G1 growth and acts through p21 expression and impaired AKT phosphorylation [45].…”
Section: Discussionmentioning
confidence: 99%
“…One study found that treatment with imatinib alone was not able to grow anaplastic cells in thyroid cancer cells, but that combination therapy (imatinib and VPA) had a cytostatic effect. This effect is mediated by stunted G1 growth and acts through p21 expression and impaired AKT phosphorylation [45].…”
Section: Discussionmentioning
confidence: 99%